Sikhism : a very short introduction - Nesbitt, Eleanor M. (Very short introductions., 2005)
An accessible introduction to the world's fifth largest religion, this work presents Sikhism's meanings and myths, and its practices, rituals, and festivals, also addressing ongoing social issues such as the relationship with the Indian state the diaspora, and caste.